Using mathematics in economics (Essex, England ; Reading, Mass. Addison-Wesley, 1999)
This text explains the basics of mathematics and how it can be used in economics. The book is an ideal introduction to mathematics for students of economics, whatever their mathematical background.
Includes bibliographical references (p. ) and index.
Keywords: Economics -- Graphic methods; Wiskundige economie